HUMAN CHROMOSOMAL ABERRATIONS CAUSED BY ELECTROMAGNITIC FIELD - ABDUL-WAHID, RAFID (Iraqi Journal of Science, 2024)
Forty five volunteers aged between 25 and 65 years ,were exposed for at least 10 years to electromagnetic fields (EMFs) induced by transmission power lines in their residential area and 15 male of similar age unexposed, away from the transmission power lines as a control group were used in this study. The electromagnetic fields (with range of 50 to 60 Hertz) were beside the homes of the volunteers. This study carried out in three different region of Baghdad and included Al –Bladyat, Hay Al-Adel and Al-Dorra region, The groups of this study were divided into three sub- groups according to the distance away from the towers of transmission power lines, (1) range: from 1 to 25 meter (2) from 25 to 50 meter (3) from 50 to 75 meter. The results showed that there were structural and numerical chromosomal abnormalities in the lymphocytes of the exposure volunteers and the frequencies of chromosomal aberrations (chromosome lose, dicentric chromosome, ring chromosome, and chromatid breaks) were significantly (P ≤ 0.05) higher than in the exposed volunteers in compare with the control group. And these aberrations increased with short distance from the transmission power lines .in all cites of this study .Additionally that we can get the high value of electromagnetic field with shorter distance from the towers of the transition power lines and this may lead to induced directly damage DNA strand and significant increase of chromosomal aberrations.